Animal Welfare and Covid-19 in Indonesia: A Neglected Legal Issue - Myrna Asnawati Safitri; Firman Firman (Hasanuddin Law Review, 2021)
The Covid-19 pandemic currently infecting the world population comes from the Coronavirus (SARS-CoV-2) transmitted initially from animals to humans, then between humans. This disease is referred to as zoonosis. Covid-19 discourse is generally about zoonotic transmission from animals to humans. Not much attention has been given to the potential transmission from humans to animals. In several countries, cases indicating the exposures of animals with the Coronavirus have been found. Thus, a discussion on the vulnerability of exposure to animals with the Coronavirus is significant to scientifically discussed. Unfortunately, concerns about this problem are still voiced by the mass media. Limited studies have been found, especially in Legal Science. In Indonesia, the Covid-19 incidence has hit more than 200 thousand people, one of the highest in Southeast Asia. Nevertheless, animal protection policy is not part of the national program of Covid-19 Control. Indonesia has several laws and regulations concerning animal welfare and zoonosis control. This article presents our study's findings investigating how the animal welfare law is applicable to protect the animals from Covid-19. Using the method of normative legal analysis, we found several weaknesses in the legal norms. We also observed how the ethics of anthro-pocentrism and ecocentrism compete in animal welfare laws.